2016
DOI: 10.1021/acscatal.6b01793
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Structure of [Mn(V)═O]: What is the Connection between Oxyl Radical Character, Physical Oxidation State, and Reactivity?

Abstract: MnVO functionalities are important in synthetic and bioinorganic chemistry, being relevant to both C–H activation and the O–O bond formation steps in enzymatic water oxidation, for example. The triplet and quintet spin states are believed to be active in these reactions, but they have only been sparingly characterized experimentally. Density functional theory (DFT) gives varying results, depending on the exchange-correlation functional employed, leading to ambiguity about whether the triplet MnVO is better r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…The stronger radical character should potentially enhance the reactivity of the ligand and thereby facilitate the oxygen–oxygen bond formation . However, for a conceptually similar Mn–oxo system, the radical character alone was found not to be crucial for a WNA …”
Section: Resultssupporting
confidence: 83%
“…The stronger radical character should potentially enhance the reactivity of the ligand and thereby facilitate the oxygen–oxygen bond formation . However, for a conceptually similar Mn–oxo system, the radical character alone was found not to be crucial for a WNA …”
Section: Resultssupporting
confidence: 83%
“…The standard procedure is to compute MS‐CASPT2 states at the GS DFT‐optimized structure. However, previous studies have shown that the use of GS DFT structures may not be appropriate and thus, some coordinates have been reoptimized with multiconfigurational ab initio methods for a particular purpose . Herein, we evaluate the variability of the MS‐CASPT2 vertical excited states with respect to the choice of the DFT‐optimized geometry for first‐to‐third‐row d 6 pseudo‐octahedral TMCs.…”
Section: Resultsmentioning
confidence: 99%
“…For those species one might draw the structure as {M --O} ← − → {M ---O}, where the formal oxidation states are M +(n -I) + O +I . Here, the +I oxidation state of the ligand highlights its electrophilic character, in the case of neutral counting 23 .…”
Section: Water Oxidation -A Mechanistic Perspectivementioning
confidence: 99%